Meridel Le Sueur's Feminist Bildungsroman: When Class Meets Gender - Núñez Puente, Carolina (Atlantis, 2006)
American and communist, Meridel Le Sueur's legacy is hardly known. On the contrary, Mikhail Bakhtin's work is currently being reread by feminist critics. Through a feminist Bakhtinian critical perspective, this article examines Le Sueur's forgotten The Girl as the feminist Bildungsroman Bakhtin only sketched out in an unpublished book.